Effects of avpr1a length polymorphism on male social behavior and reproduction in semi‐natural populations of prairie voles (Microtus ochrogaster). (17th August 2017) - Keane, Brian; Castelli, Frank R.; Davis, Haley; Crist, Thomas O.; Solomon, Nancy G.
Abstract: Intraspecific variation in sociosexual behavior has typically been investigated in the context of its relationship with environmental factors, but neurogenetic factors can also influence sociosexual behavior. In laboratory studies of prairie voles ( Microtus ochrogaster ), length polymorphism of microsatellite DNA within the gene ( avpr1a ) encoding the vasopressin 1a receptor is correlated with variation in male sociosexual behavior. However, field studies of prairie voles have found the relationship between male avpr1a microsatellite allele length and sociosexual behavior to be more ambiguous, possibly because most males had alleles of intermediate length. We tested the hypothesis that avpr1a microsatellite allele length mediates male sociosexual behavior in field settings by releasing voles into field enclosures where every male possessed two avpr1a microsatellite alleles at least one standard error longer or shorter than the mean length in their population of origin. Voles from an Illinois and Kansas population were examined separately as social monogamy appears more prevalent in the Illinois population. Illinois males with long avpr1a microsatellite alleles had smaller home ranges and overlapped a greater proportion of the home range of the female that they overlapped the most. Kansas males showed the opposite pattern. Illinois, but not Kansas, males with long avpr1a microsatellite alleles sired offspring with more females and sired more litters. Our results support the hypothesis that genetic variation associated with the avpr1a gene plays a role in mediating male prairie vole sociosexual behavior in nature. However, the relationship between specific male behaviors and male avpr1a microsatellite allele length sometimes differed significantly between Kansas and Illinois voles, suggesting relationships between specific male sociosexual behaviors and polymorphism associated with the avpr1a locus are complex, possibly involving specific nucleotide sequences or other population‐specific genetic differences.